PEDAGOGICAL PROMOTION OF PROFESSIONAL SELF-REALIZATION OF FUTURE TEACHERS OF PH ILOLOGICAL SPECIALITIES - Poseletska, Kateryna; Ihnatova, Olena; Kochenko, Olena; Hapchuk, Yana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
In the world of rapid change, the concept of professional self-realization is becoming an essential development factor for professionals. Modern teachers of philological specialties should be not only masters in their field who have indispensable professional and methodological competencies but also be ready to provide all necessary services for the current generation, which agrees with the framework of the “New Ukrainian School”. To correspond to the above-mentioned standards, a philology teacher must strive for self-development and self-improvement. The readiness of future teachers for professional self-realization is an integrated quality manifested in independent productive activity aimed at personal self-development and self-improvement. Based on theoretical research and practical experience, we have determined pedagogical conditions for the formation of readiness of future teachers of philological specialties for professional self-realization: 1) ensuring readiness for the professional self-realization of future teachers of philological specialties based on the acknowledgement of career prospects; 2) actualization of the acmeological component of the vocational training of future philologists; 3) phased inclusion of future philologists into the practically focused activity during their teaching practice. The effectiveness of these pedagogical conditions has been examined through carrying out the pedagogical experiment and a set of questionnaires and tests to define the level of readiness for professional self-realization. As a result, we have developed a system of practical classes “I am a future professional” and corrective tutorials with future teachers of philological specialties and developed common psychological and pedagogical guidelines for supervising teaching practice.